Beta-defensins in Local Antihelicobacter Defense of Gastric Mucosa in Children - N.Yu. Zavgorodnya (Zaslavsky O.Yu., 2012)
In the article there are presented the findings of investigation of production of local non-specific protective factors - beta-defensins in chronic Hp-associated gastritis in children.